Comparison of non-invasive and invasive techniques in the treatment of patients with myofascial pain syndrome - Gul, Kursat; Onal, Selami Ates (Kare Publ, 2009)
Objectives: We compared in this study the efficiency of non-invasive techniques including transcutaneous electrical nerve stimulation (TENS) and laser treatments with invasive techniques including lidocaine and botulinum toxin-A injection in patients with myofascial pain syndrome (MPS). Methods: One hundred patients who admitted to Firat University Hospital Pain Department and who were diagnosed as MPS were included in the study. Patients were randomized into four groups of 25 patients each. Sixty sessions of TENS and 20 sessions of laser treatments were performed in the first and second groups, respectively. Lidocaine and botulinum toxin-A were injected in the third and fourth groups, respectively. 2 ml (20 mg) 1% lidocaine was injected in each patient twice a week for one month in Group III. 25 U (0.5 ml) of botulinum toxin-A was injected in each patient only once in Group IV. Pain was evaluated with visual analogue scale (VAS), palpable muscle spasm scoring (PMSS) and anesthesiometer at baseline, 15, 30 and 45 days. Results: There were no statistically significant differences between the groups with respect to age, sex and education level. Pain control was statistically better in Group IV compared with the other groups with respect to VAS, PMSS and anesthesiometer scores. Conclusion: Botulinum toxin-A injection provided better pain control when compared to trigger point injection with lidocaine and non-invasive techniques including TENS and laser treatments.
Miyofasiyal a?ri sendromlu hastalarin tedavisinde non-invazif ve invazif tekniklerin karsi?laştinlmasi
Keywords: Botulinum toxin-A trigger point injection; laser; lidocaine; myofascial pain syndrome; TENS